Inorganic top electron transport layer for high performance inverted perovskite solar cells. Issue 5 (27th July 2021) - Yang, Boping; Peng, Simin; Choy, Wallace C. H.
Abstract: As promising photovoltaic devices, perovskite solar cells (PSCs) have attracted extensive and ongoing attention due to easy manufacturing and high power conversion efficiency (PCE). Although the PCE is lower than that of PSCs with normal structure, inverted PSCs have been widely investigated due to their lower hysteresis and potential application. Electron transport layer (ETL) on top of perovskite film in inverted PSCs plays a significant role in device performance. Inorganic top ETL has been used to replace organic ETL for their excellent characters. This review summarizes the progress of inorganic top ETL for high‐performance inverted PSCs. Firstly, the principles of top ETL and advantages of inorganic ETL are highlighted. Then the established top ETLs are summarized. Subsequently, various strategies for top ETL fabrication are shown to demonstrate their advantages and shortcomings. Finally, conclusion and outlook of top ETL in inverted PSCs are presented, addressing the issues and directing the hopeful solutions. Abstract : This review summarizes recent progress of inorganic top electron transport layers for high‐performance inverted perovskite solar cells, focusing on the advantages of inorganic top electron transport layers, reported inorganic top electron transport layers, and improved properties of inverted perovskite solar cells. Promising directions of future research are also suggested.